Understanding ‘Batik Belanda’ in Dutch Society via Co-Creation Experience of Creative Tourism Practice - Arlene Dwiasti Soemardi (Journal of Visual Art and Design, 2023)
Batik Belanda is a long-established acculturated cultural heritage from the Dutch East Indies era. Some examples of Batik Belanda can be seen in Batik Buketan (bouquet) and Batik Snow White (folklore). However, the representation and understanding of Batik Belanda remain deceptive. Additionally, this specific batik is still underrepresented in modern society, losing its dialogical purpose as a heritage and its connection to Indonesian and Dutch individuals’ cultural identities. Developing creative tourism is one of the solutions to promote heritage – deemed to provide a better understanding via in-depth learning and personal contact. This qualitative research was conducted in the Netherlands to analyze the potential of Batik Belanda and creative tourism practice. The creative tourism practice was done by creating an immersive batik workshop with the goal of generating interest in both Indonesian and Dutch communities in the Netherlands to connect with their cultural heritage from Indonesia. Participants’ observations and interviews with 10 workshop participants served as the main methodology. This research indicated how participants’ experiences increased their understanding of cultural heritage and fulfilled their emotional needs through the workshop, giving them motivation and shaping their interest in the pre-visit stage of cultural tourism in Indonesia. On the other hand, their interest in culture and tourism in Indonesia was divided, determined by how they perceive post-colonial subjects and their cultural identities as a community in the Netherlands.